IMPACT OF ADEQUACY OF NBFCs GOLD LOAN IN ERNAKULAM DISTRICT OF KERALA STATE (International Journal of Food and Nutritional Sciences, 2022)
India stands first in holding household stock of gold. The gold in households remain idle without generating any income. The base layer of Indian economy is still not access fully to baking services. The rural and some regions without banking service are dominated by money lenders, pawnbrokers and some forms of unorganised banking gold loan providers. However, gold loans prevent the people from debt trap. This paper provides the details of impact of the gold loan adequacy of NBFCs gold loan in Ernakulam district of Kerala state.